Antecedents and consequences of purchase regret : moderating role of brand identification - Muhammad Arslan Sarwar
Apparel fashion industry is one of the most important sectors that had been contributing to the economy of Pakistan. While it formed a major support to the national economy, this industry is facing several crucial problems which had caused a decrease in the loyalty of customers. The Steadily Increasing Discount (SID) strategies force customers to choice between the potential risk of missing the product purchase opportunities and cost savings. Though discount strategies boost up sales for brands but it also creates regret among customers as decision outcome does not live up to expectations. This study examines consumer repurchase behavior and purchases regret in the context of a SID strategy. In context of Pakistan as a developing country, the subject of discounting strategy in relation to purchase regret and role of brand identification has recently emerged as an important issue to study. This study models individual characteristic (Confirmation, Price Consciousness, Materialis , and Attractiveness of Alternatives) as a precursor of repurchase intentions and parchase regret by integrating the theoretical lens of regret theory, consumer-brand identification theory and expectancy confirmation theory. The study also examined the moderating effect of brand identification on consumer purchase regret and repurchase behavior. Random sampling technique was employed to collect the crosssectional data from respondents (Fashion Brand Buyers in Pakistan) and 317 valid responses were considered for model estimation. Data were analyzed by using Structural Equation Modeling (SEM) and for moderation analysis; the "Process" Procedures Moderation Method was applied using SPSS 21. The results suggest that confirmation, price consciousness and attractiveness of alternatives are predictors of regret and repurchase decision. For materialism it was found that materialism has a significant impact on regret but no significant impact on repurchase intention. It also indicates that consumer-brand identification attenuates the negative effects of regret on repurchase intentions. This study filled the gap and has provided a preliminary exploration of the antecedents of purchase regret by providing insights into the understandings of how and why regret can be felt and the effect can be moderated through strong brand identification. This study underscores the high-risk, high-reward nature of multiperiod pricing for managers. While firms control product availability and discount levels, they cannot control their customers' personality traits. Therefore, they should make every effort to understand their customers before embarking on such a strategy. This research takes a nomological perspective and is one of the first to look at this theoretical structure, taking into account Pakistan's apparel fashion industry.